Performance and carcass characteristics of dairy steers fed diets containing crude glycerin - Raylon Pereira Maciel; José Neuman Miranda Neiva; João Restle; Fabrícia Rocha Chaves Miotto; Luciano Fernandes Sousa; Odislei Fagner Ribeiro Cunha; Sandro Estevan Moron; Ranniere Rodrigues Pereira Parente (Revista Brasileira de Zootecnia)
ABSTRACT The objective of the study was to assess the effects of including 0, 79.8, 159.8, and 240.0 g kg-1 crude glycerin in the total diet dry matter on the 84 days feedlot performance, nutrient digestibility, blood parameters, and carcass characteristics of crossbred dairy steers. Experimental diets were composed of 98.5 g kg-1 of sorghum silage and 901.5 g kg-1 of concentrate. Twenty-four crossbred dairy steers (337.3±39.8 kg body weight and 15 months of age) were distributed in a completely randomized design with four treatments and six replicates. The intake and digestibility of the dry matter and nutrients were not altered by including crude glycerin in the diet. Crude glycerol levels did not affect the final weight (430.2 kg), daily weight gain (1.38 kg day-1), total weight gain (97.2 kg), hot carcass weight (218.9 kg), cold carcass weight (215.2 kg), hot carcass yield (0.50 kg 100 kg-1 BW), longissimus dorsi area (62.86 cm²), subcutaneous fat thickness (4.05 mm), and carcass physical composition. Concentrations of serum glucose, triglycerides, total cholesterol, high-density lipoprotein cholesterol, and creatinine were not altered by including crude glycerin in the diet. Crude glycerin can be added to high concentrate diet up to 240 g kg-1 without changing the animal performance, apparent digestibility of nutrients, the main carcass characteristics, and blood parameters of finishing crossbred dairy steers.